EU trade pattern. - Lim, Heng Hai. (2008)
Our project seeks to analyse the trends in trade among the fifteen countries in the EU, and between those countries and Rest of Europe, the United States, Asia and Others. We will also attempt to examine the relationship between trade and economic integration.